The Importance of the Legal Culture of the Pluneng Village Community as an Effort to Preserve Water Resources - Pinasti, Kana Jihan; Suhadi, Suhadi (Jurnal Ragam Pengabdian, 2026)
This study examines the importance of legal culture in the Pluneng Village community as an effort to preserve water resources within a socio-legal framework. The research employs a qualitative method with a sociological legal approach, utilizing field observations, in-depth interviews, and document analysis to explore the interaction between formal law and living law. The findings reveal that legal culture, manifested through local traditions such as Syukur Banyu, functions as a primary driver of community compliance in water conservation practices. These culturally embedded norms operate alongside formal legal frameworks and strengthen environmental governance through collective awareness and participation. The study also identifies the institutional role of village authorities and community organizations in integrating local wisdom into practical conservation strategies. Empirical evidence shows that such integration contributes to maintaining water quality, reducing pollution, and ensuring resource sustainability. The research highlights that the effectiveness of water resource management is closely linked to the internalization of legal values within society. The study concludes that strengthening legal culture is essential for achieving sustainable and community-based water conservation.